Pengelolaan Jurnal Elektronik Bidang Perpustakaan Menuju Jurnal Terakreditasi - Sri Junandi (Institut Agama Islam Negeri Salatiga, 2018)
The management of scientific journals in order to achieve national accredited scientificjournals requires an effective and efficient Journal Management and ManagementSystem. Management and Management Systems This journal should refer tothe instruments and criteria required by the accreditation of national journals andinternational indexing agencies. Periodical Manager of Library and Information Sciencehas implemented most of the instruments and criteria set out in accordance withthe Director General of Hig. Periodical Manager of Library and Information Sciencehas implemented most of the instruments and criteria set out in accordance with theDirector General of Higher Education Directive No. 1 2014 on Guidelines for Accreditationof Scientific Periodic Issue. In addition BIP managers are actively following thedevelopment related to the management of journals by attending workshops, training,mentoring, electronic journals governance grants, accreditation of scientific journals,journal indexation. Armed with genuine efforts and willingness Periodic Library andInformation Sciences managed to qualify to achieve accreditation status as the firstaccredited library of science journals in Indonesia with Decree No. 51 / E / KPT / 2017valid for five years ahead of the period 2017-2022. Armed with genuine efforts andwillingness Periodic Library and Information Sciences managed to qualify to achieveaccreditation status as the first accredited library of science journals in Indonesia withDecree No. 51 / E / KPT / 2017 valid for five years ahead of the period 2017-2022.